2001
DOI: 10.1002/1097-0274(200103)39:3<320::aid-ajim1020>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations of trichloroacetic acid in Danish workers exposed to trichloroethylene, 1947-1985

Abstract: Background Since 1947, the National Labour Inspection Service in Denmark has relied upon urinary measurements of trichloroacetic acid (TCA) in surveys of the occupational exposure to trichloroethylene (TCE). Methods We examined the paper files relating to 2397 TCA measurements to extract information about the year, the company, the work process and the worker. We used multiple regression models to analyze the effects of various factors on the urinary concentration of TCA. Results The regression analyses showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The results of a recent study of concentrations of the TCE metabolite trichloroacetic acid (TCA) in the urine of Danish workers (31) are in agreement with several of the ndings of this study: 1) concentrations of TCA decreased markedly from 1947 to 1985; 2) relatively high concentrations were found in workers from the iron and metal industry; and 3) TCA levels were two times higher among men than among women workers in the iron and metal industry. The study found higher TCA levels among younger than among older workers, whereas in this study, age was not signi cantly associated with exposure to TCE.…”
Section: Table IVsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of a recent study of concentrations of the TCE metabolite trichloroacetic acid (TCA) in the urine of Danish workers (31) are in agreement with several of the ndings of this study: 1) concentrations of TCA decreased markedly from 1947 to 1985; 2) relatively high concentrations were found in workers from the iron and metal industry; and 3) TCA levels were two times higher among men than among women workers in the iron and metal industry. The study found higher TCA levels among younger than among older workers, whereas in this study, age was not signi cantly associated with exposure to TCE.…”
Section: Table IVsupporting
confidence: 81%
“…Particularly in the dry-cleaning industry, a number of other halogenated solvents such as perchloroethylene and Freon 113 have been used. A very limited amount of mixed solvents have been used as spotting agent during the whole calendar period but the switch to these other chemicals as the solvent of choice, however, typically occurred in the 1970s and 1980s, (31) and the vast majority of the nonspeci c TCE measurements occurred before 1960. The possibility of in uential interferences cannot be excluded but would probably be a relatively rare phenomenon.…”
Section: Table IVmentioning
confidence: 99%
“…Moreover, these workers were likely exposed to other solvents that may also produce U-TCA as a metabolite (National Research Council of the National Academies 2006). Raaschou-Nielsen et al (2001 investigated the factors related to TCE exposure among Danish workers in various industries. In general, there was agreement between estimated air concentrations and U-TCA concentrations regarding decreasing levels of exposure over time, relatively high concentrations in the iron and steel industry, including airplane maintenance, and higher levels of exposure among men than women.…”
Section: Exposure Assessment Limitationsmentioning
confidence: 99%
“…In addition, the levels of TCAA in urine (Bloemen et al 2001;Fisher et al 1998;Raaschou-Nielsen et al 2001;Vartiainen et al 1993) and in plasma (Ziglio 1981) have been used as a biomarker for occupational or unintentional exposure to trichloroethylene, (TCE), a compound that is partially metabolized to TCAA in humans.…”
mentioning
confidence: 99%